IMF Staff papers : Volume 25 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1978)
This paper considers whether the objective of controlling aggregate reserves is still appropriate under current international monetary arrangements and discusses some of the means that have been proposed to achieve such control. Both the demand for and the supply of world reserves have changed as a result of the shift to flexible exchange rates and the growth of private capital markets as means of financing payments disequilibria. Mechanisms designed to achieve greater control over reserve growth would have to rely on direct constraints on individual countries. The desirability of imposing such constraints must be assessed in the light of how effective liquidity control can be in achieving the objective of more timely and effective adjustment. In this connection, the surveillance of exchange rate policies provided for in the IMF's Proposed Second Amendment to the Articles of Agreement may be a more effective weapon than direct control of liquidity.